Optimalisasi Produksi dan Pemasaran Gula Kelapa Melalui Standarisasi Wadah Nira Pasca Panen dan Kemasan Beridentitas Lokal di Kelompok Tani Gula Kelapa Gendis Asri - Faturohman, Muhammad Iqbal; Pratama, Aiza Yudha; Utami, Gladi Pawestri (Politeknik Piksi Ganesha Indonesia, 2026)
The Gendis Asri Coconut Sugar Farmers Group in Pernasidi Village, Cilongok District, Banyumas, is one of the coconut sugar producers with great potential but faces challenges related to production quality and marketing. The main issues identified include the low quality of sap after harvesting due to the use of unhygienic plastic jerry cans, as well as weak marketing strategies caused by unattractive product packaging that lacks local identity. This community service program aims to improve production quality and product competitiveness through the replacement of sap containers with food-grade HDPE materials, the provision of climbing belts to enhance work safety, the installation of continuous band sealers and digital scales, and the development of culturally inspired packaging designs based on Cilongok’s local heritage. The implementation methods include socialization, training, mentoring, and technology application. The results show a significant increase in the quality of collected sap, improved product readiness for entry into modern markets, and strengthened farmer capacity in both production and marketing aspects. This program has had a positive impact on product quality, work safety, process efficiency, and the branding readiness of local coconut sugar products.